Spectral and Theoretical Studies of The Stability Constant of Charge Transfer Complexes of A Number of Schiff Bases With Eu(Fod)3 in Different Solvents - Saleem, Layla M. Najeeb; Al-Hyali, Emad A. Saleh; Al-Taei, Feda H. Marie (Science Journal of University of Zakho, 2013)
The equilibrium constants (K) of charge transfer complexes (CTC) of salicylidene amino pyridines and salicylidene aniline with lanthanide shift reagent Eu(fod)3 in different solvents were determined by applying Benesi- Hildebrand equation. The effect of the polarity of the solvent, electronic factors and steric effect were investigated. Structural and energetic parameters like bond lengths, bond angles, energies of HOMO and LUMO orbitals, η, µ, and ω were obtained by quantum mechanical calculations employing semi empirical model (Austin Method1, AM1). The theoretical parameters are used to illustrate the ambiguities and support the explanation of the experimental results.